Determining the post-operative opioid requirements of patients post total abdominal hysterectomy with a bupivacaine infusion in the incisional site - Russell, Samantha Lee (My University, 2010)
Postoperative pain is prevalent and not optimally managed in most patients. Pain can lead to adverse emotional and systemic consequences. Numerous device orientated studies have been done in other countries looking at the effect of infusions of local anaesthetic at the wound site postoperatively via an elastomeric pump. There have however been no similar studies done in South Africa. The aims of this study was to assess whether the use of an incisional wound catheter and 0.39% bupivacaine infusion in patients post total abdominal hysterectomy for a 30 hour period will decrease opioid requirements compared to a control group having only systemic analgesia. Pain intensities were also documented at set observation periods. The opioid requirements between the 2 groups were comparable however the participants who had the bupivacaine infusion in their incisional site had less pain intensity scores until 6 hours post operation and had less pain intensity on movement at 30 hours post operation. A bupivacaine infusion in the incisional site decreases pain intensity in the above mentioned parameters but does not reduce opioid requirements.
MMed, Faculty of Health Sciences, University of the Witwatersrand
Keywords: abdominal hysterectomy; pain management